2023
DOI: 10.3389/fcvm.2023.1102502
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-based aortic flow profile characterization with 4D phase-contrast MRI

Abstract: 4D PC MRI of the aorta has become a routinely available examination, and a multitude of single parameters have been suggested for the quantitative assessment of relevant flow features for clinical studies and diagnosis. However, clinically applicable assessment of complex flow patterns is still challenging. We present a concept for applying radiomics for the quantitative characterization of flow patterns in the aorta. To this end, we derive cross-sectional scalar parameter maps related to parameters suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…36 In addition, recent approaches combined radiomic feature extraction with classification algorithms for the detection and understanding of clinical phenotypes, leveraging the explainability of the approach for hypothesis generation and quantitative characterization of cardiovascular pathologies. 37,38 The development of such explainable radiomics/AI solutions in cardiac imaging is a field of ongoing research. Salih et al 39 cardiac imaging.…”
Section: Step 3: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In addition, recent approaches combined radiomic feature extraction with classification algorithms for the detection and understanding of clinical phenotypes, leveraging the explainability of the approach for hypothesis generation and quantitative characterization of cardiovascular pathologies. 37,38 The development of such explainable radiomics/AI solutions in cardiac imaging is a field of ongoing research. Salih et al 39 cardiac imaging.…”
Section: Step 3: Image Processingmentioning
confidence: 99%
“…27 Some authors could demonstrate that through adapted preprocessing, comparability of higher-order radiomics features could be achieved. 38,72,73 Recently, the AutoRadiomics platform has been introduced 30 as an intuitive open-source framework enabling reproducible radiomics research via an interactive graphical user interface. Nevertheless, is has been shown that even with standardized image-processing methods, only limited success was evident regarding robustness and reproducibility.…”
Section: Lack Of Standardization and Reproducibilitymentioning
confidence: 99%
“…By analyzing features from medical images, radiomics may create accurate prediction models to support clinical decision-making (Felfli et al, 2023;O'Donnell et al, 2022). The potential applications of radiomics are broad and span various medical fields, including oncology, neurology, and cardiology (Cassinelli Petersen et al, 2022;Huellebrand et al, 2023;Lambin et al, 2017;Santos et al, 2023).…”
Section: Introductionmentioning
confidence: 99%